2020
DOI: 10.3390/jcm9020344
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Bases of Neurodegeneration and Cognitive Decline, the Major Burden of Sanfilippo Disease

Abstract: The mucopolysaccharidoses (MPS) are a group of diseases caused by the lysosomal accumulation of glycosaminoglycans, due to genetic deficiencies of enzymes involved in their degradation. MPS III or Sanfilippo disease, in particular, is characterized by early-onset severe, progressive neurodegeneration but mild somatic involvement, with patients losing milestones and previously acquired skills as the disease progresses. Despite being the focus of extensive research over the past years, the links between accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 192 publications
(401 reference statements)
1
56
0
Order By: Relevance
“…In several LSDs, including MPSs, secondary storage of substrates that are not explained by the primary lysosomal defect has been consistently documented. The types of secondarily stored compounds are highly heterogeneous and include glycosphingolipids, phospholipids, and cholesterol [22][23][24][25][26][27]. Secondary storage has been described both in patients affected by MPSs and in animal models from different species.…”
Section: Secondary Storagementioning
confidence: 99%
See 1 more Smart Citation
“…In several LSDs, including MPSs, secondary storage of substrates that are not explained by the primary lysosomal defect has been consistently documented. The types of secondarily stored compounds are highly heterogeneous and include glycosphingolipids, phospholipids, and cholesterol [22][23][24][25][26][27]. Secondary storage has been described both in patients affected by MPSs and in animal models from different species.…”
Section: Secondary Storagementioning
confidence: 99%
“…The impairment of the autophagic flux has been recognized as important pathogenetic factor for neurodegeneration in lysosomal storage diseases, including MPSs [27,55]. In neurons, basal levels of autophagy are essential for neuronal function and survival, since they prevent toxic proteins from reaching harmful concentrations and contribute to the degradation of aged or damaged organelles, such as mitochondria [56,57].…”
Section: Abnormal Autophagymentioning
confidence: 99%
“…In LSDs, reduced autophagic flux has been shown to lead to the persistence of dysfunctional mitochondria with a consequent increase in reactive oxygen species production, altered calcium homeostasis, and enhanced pro-apoptotic signals [43,61,62]. Moreover, many studies have shown that defective mitochondrial activity contributes to neuroinflammation and cognitive defects in different MPS III mouse models [63,64]. These findings on the diffuse presence of defective mitochondria in many MPS diseases support our results relating to impaired β-oxidation-related pathways in MPS IIIB mice.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients who present the first symptoms after the neonatal period, the ones who suffer from the severe forms of MPS I, II, and VII have both somatic and cognitive involvement [ 31 ]. Still, there is a subtype of MPSs, which is characterized by an extremely severe neurological phenotype, although exhibiting little or no somatic involvement: the MPS III or Sanfilippo syndrome (reviewed in [ 26 , 35 ]). The characteristic feature in MPS III is that of a child who presents with normal development until the age of 12 to 18 months and then fails to develop normal speech.…”
Section: Lysosomal Storage Disordersmentioning
confidence: 99%
“…Such behavior is characterized by severe insomnia and extreme hyperactivity, which makes disease management extremely difficult. As the disease progresses, patients may also develop autistic behavior (reviewed in [ 35 ]). Then, skills are lost, and the children become unsteady and fall frequently, tending to develop neurological dysphagia.…”
Section: Lysosomal Storage Disordersmentioning
confidence: 99%